2022
DOI: 10.1364/oe.452767
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human ovarian cancer relying on collagen fiber coverage features by quantitative second harmonic generation imaging

Abstract: Ovarian cancer has the highest mortality rate among all gynecological cancers, containing complicated heterogeneous histotypes, each with different treatment plans and prognoses. The lack of screening test makes new perspectives for the biomarker of ovarian cancer of great significance. As the main component of extracellular matrix, collagen fibers undergo dynamic remodeling caused by neoplastic activity. Second harmonic generation (SHG) enables label-free, non-destructive imaging of collagen fibers with submi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…It has been shown that there is a link between the progression of cancer and the alteration of its surrounding collagen fibers [34][35][36]. To obtain the quantitative information of collagen fibers surrounding normal pancreatic ducts and different grades of PanIN, we extracted eight morphological features of the collagen fibers surrounding the ducts from MPM images by an automated image processing strategy.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…It has been shown that there is a link between the progression of cancer and the alteration of its surrounding collagen fibers [34][35][36]. To obtain the quantitative information of collagen fibers surrounding normal pancreatic ducts and different grades of PanIN, we extracted eight morphological features of the collagen fibers surrounding the ducts from MPM images by an automated image processing strategy.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…For waviness, a higher value represented curvier status. Local coverage was another metric that quantified the voxel-wise localized distribution of fibers [ 45 ]. The value of local coverage also ranged from 0 to 1 with a higher value corresponding to morphologically denser fiber distribution in a local area.…”
Section: Experimental Model and Subject Detailsmentioning
confidence: 99%
“…Based on orientation information, we further proposed optical metrics, named directional variance and waviness, respectively, as quantitative measures of alignment and bending degree of fibers, and applied them to mapping physiological and pathological functions of collagen fibers in articular cartilage, mammary glands, breast tissues, ovarian tissues and pancreas, in the context of diseases including osteoarthritis and cancer [ [41] , [42] , [43] , [44] ]. Besides, we developed an algorithm for the quantification of morphologically localized distribution of fiber-like structures, termed local coverage, which provided new insights into the spatial organization of fibrous tissues [ 45 ]. Importantly, by extracting 3D information, these optical metrics faithfully reflected the real architecture of biological tissues.…”
Section: Introductionmentioning
confidence: 99%
“… 19 , 20 In addition, alterations in morphology and organization of collagen and elastin fibers, the major components of the ECM, are closely associated with physiologic and pathologic status of biological tissues. 21 25 Compared with traditional pathological methods, multiphoton imaging technology has great benefits in simplifying sample preparation. In the pathological method, it requires fixing the tissue sections with paraffin and staining them.…”
Section: Introductionmentioning
confidence: 99%